Escaping Immoral Plants: the Dynamic of Access and the Moral Economy of Tobacco Farming on the Slopes of Sindoro-Sumbing - Priharwanto, Novi (Masyarakat: Jurnal Sosiologi, 2024)
In recent years, tobacco farmers on the slopes of Mount Sindoro and Sumbing (Sinsu), Central Java, have experienced a downturn due to the increasingly falling price of dry chopped tobacco. Instead of making a profit, they are in debt to middlemen, which they may not be able to pay off until the next planting season. As a result, many of the farmers decided to switch to agricultural cultivation or quit tobacco altogether. This research argues that the process of the farmers’ leaving tobacco is also influenced by the dynamics of access and the moral economy, as manifest in the metaphor of the "immoral plant". This research applied ethnographic method to trace the long flow of tobacco distribution which contains moral economic practices and complicated access mechanisms which tend to be detrimental to tobacco farmers. The research was conducted using ethnographic methods on three groups of farmers, namely: farmers who continued to grow tobacco in the dry season, then switched to planting vegetables in the rainy season; farmers switching completely to vegetable crops; and farmers who looked for other professions outside of agriculture.